A survey to better understand the performance measurement dimensions for Australasian nonprofit healthcare organisations: data summary report - Soysa IB; Jayamaha NP; Grigg NP (Massey University, 2016)
This report has been especially prepared for those who responded to our survey, which was designed to test the performance measurement system that we developed for Australasian healthcare nonprofit organisations (NPOs). The performance measurement (PM) system itself was developed through extensive case studies involving nine Australasian NPOs (six from New Zealand and three from Australia). Figure 1 shows our PM Framework. The report provides key findings from a survey recently conducted by us to test the PM framework that we developed through case studies (some details of the case studies have been described). Our performance framework was found to be reliably generalisable across Australasian NPOs in the healthcare sector. The framework is therefore useful for performance monitoring and improvement of healthcare NPOs in the region. An online questionnaire was used to collect the data from senior managers belonging to healthcare NPOs across Australia and New Zealand. Out of the 1550 senior managers invited to participate in the survey, 232 responded, resulting in a response rate of 15%, which is considered satisfactory for this type of a survey. We found that the most survey participants were familiar with PM systems. The study validated the nine PM domains (categories) in our framework, namely Mission; Strategy; Organisational Infrastructure; People; Financial Health; Process; Client Satisfaction; People Satisfaction and Donor Satisfaction. The survey showed that out of the 41 survey questions (items) allotted to the nine PM domains, five are incompatible with the PM framework (they do not relate to any of the nine PM dimensions of our model); these have been removed from the final analysis. We found that out of the 36 valid survey items considered, organisations performed exceptionally well in 6 items (Q3, Q5, Q20, Q1, Q17 and Q27), reasonably well in 27 items, and moderately well in 3 items (Q34, Q7, and Q41); see Table 2 for definitions as well as results. The study confirmed that the organisation has to be driven by their directors and the senior leadership in order to achieve better performance. This includes understanding and developing the people within the organisation. We found that the processes put in place by the organisations to achieve stakeholder satisfaction can be divided into three types: continuous improvement; designing of safe, efficient and effective processes; and designing of the infrastructure, technology and material to create the necessary support processes. We also found that the three key stakeholders of NPOs — clients (or customers), employees, and donors — carry approximately equal weight in achieving the mission. Each of these stakeholder groups has their own set of expectations and these expectations belong to three themes: delivering high quality services and support to the community; valuing skilled workers and recognising people (volunteers included); and commitment to social responsibility. The complementary Microsoft Excel spreadsheet that we have provided helps organisations to conduct self-assessments on organisational performance. This in turn helps an organisation to identify: (a) best practices for process improvements, (b) trends in performance management practices, benchmark practices and (c) relationships between performance and stakeholders and organisational performance.